2017
DOI: 10.1007/s00520-017-3743-3
|View full text |Cite
|
Sign up to set email alerts
|

Instruments to measure anxiety in children, adolescents, and young adults with cancer: a systematic review

Abstract: We identified 14 different multi-item and 13 different single-item anxiety measurement instruments that have been used in pediatric cancer or HSCT. Only three multi-item and two single-item instruments were identified as being reliable and valid among pediatric cancer or HSCT patients and would therefore be appropriate to measure anxiety in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…We recently conducted a systematic review of instruments used to measure anxiety in children and adolescents receiving chemotherapy or undergoing HSCT . We identified 14 different multi‐item and 13 different single‐item anxiety measurement instruments that have been used in pediatric cancer or HSCT .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently conducted a systematic review of instruments used to measure anxiety in children and adolescents receiving chemotherapy or undergoing HSCT . We identified 14 different multi‐item and 13 different single‐item anxiety measurement instruments that have been used in pediatric cancer or HSCT .…”
Section: Discussionmentioning
confidence: 99%
“…We recently conducted a systematic review of instruments used to measure anxiety in children and adolescents receiving chemotherapy or undergoing HSCT . We identified 14 different multi‐item and 13 different single‐item anxiety measurement instruments that have been used in pediatric cancer or HSCT . Review of identified instruments and application of the COnsensus‐based Standards for the selection of health Measurement INstruments (COSMIN) checklist, which aids in evaluation of the methodological quality of studies on the measurement properties of health measurement instruments, or guiding questions such as those put forth by Coster could be considered as a next step to aid in selection of an anxiety measurement instrument for use in this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, there is a lack of well-defined and reliable pediatric COA tools in the pediatric neurooncology population, given the heterogeneity in developmental abilities and requirements for age-defined instruments. However, tools such as the Patient-Reported Outcomes Measurement Information System (PROMIS) 69 are increasingly being incorporated as part of pediatric evaluations, [70][71][72][73][74] and several pediatric instruments are under development. Their use in assessing response in pediatric patients is encouraged although not required at present.…”
Section: Neuro-oncologymentioning
confidence: 99%
“…State trait anxiety inventory for children: It is the gold standard test for assessing anxiety. The State-Trait Anxiety Inventory for Children (STAI-CH) differentiates between general tendency to anxious behaviour rooted in the personality and anxiety as a fleeting emotional state [7]. The test is designed to be used with primary or junior high school children and consists of two 20 item scales.…”
Section: Anxiety Assessmentmentioning
confidence: 99%